EFEKTIVITAS TYPE MESH SIZE YANG BERBEDA PADA ALAT TANGKAP GILL NET DASAR (BOTTOM GILL NET) TERHADAP HASIL TANGKAP IKAN: Effectiveness Of Different Type Mesh Sizes In Base Gill Net Capture Tools (Bottom Gill Net) On Fish Catching Results - Hartawan Hartawan; Raismin Kotta; I Nyoman Budi Satriya; Azhari Tarmizi (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2023)
This study aims to determine the effectiveness and differences in the results of different types of Mesh sizes using Basic Gill Net Fishing Equipment (Bottom Gill Net) on fish catches, and to determine the composition of the types of fish caught. The method used in this study was an experimental method with a completely randomized design (CRD). The research was carried out in the waters of Puyahan Hamlet, Lembar Selatan Village, Lembar District, West Lombok Regency. The results of the study based on Sidik Diversity Analysis (ANASRA) showed that there was a "very significant" different effect on the different Mesh size type treatments in units of weight (kg) where (F count 10.43 > F table 1% 5.95). The results also showed that the types of fish caught during the study used 4 types of mesh sizes on basic gill nets, with the most in treatment 1st repetition 3 as much as 4.9 kg and the least in treatment 4th repetition 2 as much as 1 kg. overall the highest catch was obtained in treatment 1 (mesh size 1.5 inches) as much as 16.9 kg (36.03%) and the least was obtained in treatment 4 (mesh size 2.5 inches) as much as 7.4 kg ( 15.80%). The types of fish caught are: Lemuru, Rajungan, Grouper, Tembang, Beronang, Layur), white pomfret, seed jackfruit/kuniran, Tiga waja.